Pragmatic Analysis On The Language Expression Used In Super-T T-Shirt - Bahrudin., Anang; , Drs. Sigit Haryanto, M. Hum; , Dra. Dwi Haryanti, M. Hum (2013)
This study focuses on analyzing language expression used in SUPER-T T-SHIRT using the theory of speech act by Austin.This research is aimed at 1) describing language form used in SUPER-T T-SHIRT, 2) describing locution and illocution of the language form used inSUPER-T T-SHIRT. In collecting data, the writer uses documentation method by collecting sentences on SUPER-T T-SHIRT, rewriting all sentences on the SUPER-T T-SHIRT and collecting the data. In decribing language form and locution and illocutionary act, the writer refers to the context of situation proposed by Austin. Having been analyzed the data, the writer found that speech act theory can be found in SUPER-T T-SHIRT. The result show that 1) there are 6 or 20% data of phrase, 2 data or 6.67% data of clause, and 22 data or 73.33% data of sentence that consist of 14 data of imperative sentence and 8 data of declarative sentence. The last is 2) describing locution and illocution of the language form used inSUPER-T T-SHIRT, the result show there are 15 or 50% data of representative utterance and 15 or 50% data of persuasive utterance.